Comparison of the Anterior Tooth and Lip Esthetic Characteristics of Hani and Han Youth in China When Speaking - Yang LL; Peng P; Lin YH; Zhou T; Ren XX; Wang WQ; Li XX (Dove Medical Press, 2021)
Li-Li Yang,1,2,* Ping Peng,1,3,* Yun-Hong Lin,3 Ting Zhou,4 Xiao-Xue Ren,1,3 Wei-Qi Wang,1 Xing-Xing Li1,3 1Department of Dental Research, The Affiliated Stomatological Hospital of Kunming Medical University, Kunming, Yunnan, 650100, People’s Republic of China; 2Department of Periodontics, The Affiliated Stomatological Hospital of Kunming Medical University, Kunming, Yunnan, 650100, People’s Republic of China; 3Department of Prosthodontics, The Affiliated Stomatological Hospital of Kunming Medical University, Kunming, Yunnan, 650100, People’s Republic of China; 4Department of Orthodontics, The Affiliated Stomatological Hospital of Kunming Medical University, Kunming, Yunnan, 650100, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xing-Xing LiDepartment of Prosthodontics, The Affiliated Stomatological Hospital of Kunming Medical University, No. 1088 Haiyuan Road, Wuhua District, Kunming, Yunnan, 650100, People’s Republic of ChinaTel +86 13759581696Fax +86 87165330099Email lxx_drli1862@163.comObjective: This study aims to measure and analyze the lip and tooth dynamic esthetic characteristics at rest and during speech in order to provide a reference for its esthetic design and restoration among the Hani and Han populations in Yunnan Province, China.Methods: Subjects of Hani and Han ethnicity in Yunnan were selected using multistage stratified sampling and inclusive criteria. The lip and tooth dynamic esthetic characteristics of the subjects at rest and during the pinyin pronunciation of “me”, “yi”, “fu”, and “si” were recorded using digital photography and analyzed with computer software.Results: No statistical difference was detected between the Hani and Han groups in the upper central-incisor display, when pronouncing the pinyin “yi”. Furthermore, there were no statistical differences in lip dynamic esthetic parameters between the Hani and Han groups, except for the distance between the upper and lower lips when pronouncing “si”. There were three kinds of correlation between the upper central-incisor edge and lower lip: separation, contact, and overlap.Conclusion: The display of upper central incisors and the mouth width of Hani people are larger than those of Han people when at rest. When the pinyin “si” is pronounced, the display of upper central incisors and the upper–lower lip distance of Hani people is less than that of Han people due to labial muscle movement.Keywords: Hani, Han, pronunciation, lip and tooth aesthetics, digital videography